Drug treatment of insomnia - Serra, Joana (2006)
Insomnia is a complaint with multiple etiologies, with varying degrees of severity and duration. Careful evaluation is indispensable to ensure the selection of an effective treatment. Pharmacological treatment is an alternative therapeutic approach of insomnia, and sedative-hypnotic drugs the most prescribed drugs in medical practice. For greater efficacy and side effect profile, receptor agonists omega-benzodiazepine hypnotics is considered one of first choice.